Analysis of problems and policy suggestions in the construction of business environment in China - CAO Yonghui; JIANG He (E3S Web of Conferences, 2020)
Building a good business environment is of positive significance for the healthy growth of enterprises and the high-quality development of China’s economy. China has achieved positive results in recent years, but there are still problems in some aspects, which has become an obstacle to the further development of China’s economy. Therefore, based on the actual situation of our state-owned business environment, this paper focuses on the core problems, analyzes the causes and puts forward relevant policy recommendations. This paper mainly analyzes the construction of government environment, business law environment and the internationalization of business environment, so as to provide reference and reference for the high quality of China’s economy.